PENERAPAN CHATBOT UNTUK JURUSAN TEKNIK ELEKTRO - Marya, Dianthy; Ardiansyah, Rizky; Novianti, Atik (Universitas Islam Balitar, 2025)
High-quality campus services play a crucial role in supporting educational activities in higher education institutions. One approach to enhancing these services is by leveraging chatbot technology. Chatbots can provide swift and efficient responses to students, simplifying access to information and facilitating various transactions. Moreover, chatbots help reduce the workload of administrative staff, allowing them to concentrate on more complex responsibilities. However, data security and privacy remain critical aspects that require further improvement to ensure user trust. This study focuses on evaluating a chatbot application designed to support administrative services in the Electrical Engineering Department of the State Polytechnic of Malang using the string matching method. The evaluation process includes testing the chatbot’s functionality, interaction quality, compatibility, security, and overall performance. Results indicate that the chatbot achieves an accuracy rate of 90% in addressing students’ inquiries. Most users expressed satisfaction with the chatbot’s response speed and precision. These findings suggest that chatbots are an effective solution for improving administrative services, particularly in the context of the Electrical Engineering Department at the State Polytechnic of Malang.